(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The aim of this paper is to show a case of a patient with a transversal deficience of maxillae treated to make rehabilitation in the anterior area. The diagnosis of dentofacial deformities was realized using routine studies incorporating image and clinical analysis to observe the bilateral posterior crossbite and abnormal position in tooth 11 and 21; the 11 showed alterations in bone and teeth with no possibilities to make the prosthetic treatment making the dental extraction. Later, was realized the installation of the implant and the rehabilitation with fixed prosthesis. Is discussed the treatment and the options used in the approach. Was concluded that the integration of diagnosis dental, skeletal and facial could make an adequate therapy in complex cases.